THE INFERIORITY FEELING OF THOMAS SUTPEN REFLECTED IN WILLIAM FAULKNER'S ABSALOM ABSALOM!: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - NURUL H , DWI UTAMI (2007)
The problem statement of this study in how inferiority feeling influences Thomas sutpen personality development. There are two objectives of the study. The first the research tries to analyze the novel based on Adler's theory of individual psychology. The second objective is to analyze the novel based on it's structural elements. This study belongs to qualitative study. In this method the researcher uses two data sources. The primary is the novel Absalom-absalom! and secondary is materials related to problem of the study the data collection is documentation and technique of data analysis in this study is descriptive. The result of the research shows that unsolved inferiority feeling that may contribute to the bad character building. Thomas sutpen feels inferior of being poor white man. However, his weaknesses made to strive to be a rich person. This expectation always motivates him to work hard and to overcome everything that my foil his goal. Thus, he is willing to do anything wrong morally and socially. Indirectly, it influences to his immoral life style. By his excessive ambition, he also tends to withdraw from society so many societies in his country hate him. His creative power to escape from poverty appears experiencing the traumatic event, for example in his trying to leave West Virginia, and his trying to seek respectability. Finally, inferiority feeling contributes his imbalance to adjust his behaviour to the society's role.